Inventory of the scientific potential of the lunchboxes (weathering pits) in the district of Fazenda Nova, Pernambuco, Northeast Brazil - Lima, Gerlando Rodrigues de; Listo, Danielle Gomes da Silva; Guimarães, Thaís de Oliveira; Arruda, Ítalo Rodrigo Paulino de (Geologia USP. Série Científica, 2023)
Weathering pits correspond to depressions originating in granite rocks and are considered as a unit of landscape because they are existing geoforms on the surface. These geosites have a scientific value because had serve in the past as storage areas for sediments and bones of the Pleistocene megafauna, probably associated with non-functional drainage contexts under the current semi-arid climate. That way, the objective of the research was the inventory of the weathering pits located in the district of Fazenda Nova, semi-arid Pernambuco, seeking to establish indexes of its scientific potential for future policies and instruments ofmanagement of these assets at the regional level. The first stage of the inventory process was organized through a form that had the role of identifying and morphologically characterizing the distribution of weathering pits and the second was carried out following the usual method of quantification for scientific value. Considering the weathering pits presented in the context of the inventory carried out in this study, it reinforces the certainty that this heritage, considered as a geomorphosite, holds in its conjuncture the evolutionary history of the landscape diverse geomorphologicaland geological information, which are pertinent information of that region, or may go beyond these contributions, because these geomorphosites have scientific value, which are correlated with several sciences, then its use can provide quite significant discoveries, regarding its scientific use.